Bulge micro-textures influence on tribological performance of ultra-high-molecular-weight-polyethylene (UHMWPE) under phosphatidylcholine (Lipid) and bovine serum albumin (BSA) solutions. (28th March 2019) - Sufyan, Muhammad; Hussain, Muzamil; Ahmad, Hassaan; Abbas, Naseem; Ashraf, Jawaria; Zahra, Nida
Abstract: Ultra-High Molecular Weight Polyethylene (UHMWPE) is an engineering polymer used as a bearing material with metallic or ceramics counter surfaces in orthopedic implants because of its high ductility, compatibility and impact resistance. Several methods, including cross-linking, surface texturing and particle or fiber reinforcement have been employed to improve the tribological performance of UHMWPE. In this study, square and rectangular bulge textures were introduced on UHMWPE and their influence on friction and wear properties under Phosphatidylcholine (Lipid) and Bovine Serum Albumin (BSA) solutions were investigated. The laser texturing was performed under different conditions such as using distilled water layer, aluminum foil and at freezing and room temperature with varying laser processing parameters including scanning speed, pulse frequency, and laser intensity. The textures in the required dimension were produced using only aluminum foil by controlling melt viscosity. The ball-on-disk tribometer was used for tribological tests. The reduction in coefficient of friction (COF) was recorded in case of textured specimens as compared to un-textured specimens at low concentration of BSA and at higher concentration of lipid. However for both cases, the square texturing was proved optimal as compared to rectangular texturing because of the higher area ratio of square textures.